Płaskie drgania swobodne niepodpartych pierścieni kołowych.Część II. Formy drgań własnych - OLSZOWSKI, Bogdan (Engineering Transactions, 1990)
W pracy omówiono analizę porównawczą płaskich form drgań własnych różnych typów modeli uściślonych, przestrzennie swobodnych pierścieni kołowych. Analiza ta stanowi dalsze rozwinięcie tematu prezentowanego w publikacji [1] tylko w aspekcie porównań częstości drgań 'własnych. Free in-plane vibrations of unsupported circular rings part ii. Natural modes The aim of the paper is a comparison of natural modes obtained numerically for different types of ring model s taking into account extension, rot ary intertia and shear deformation. Special attention is laid on the singularities appearing in two cases when the wavenumber is equal to zero or one.